Conceptual histories and critical theories. (February 2016) - Gilbert, Andrew
Recent scholarship has drawn on Koselleck's methods of conceptual history and his diagnosis of 'crisis' in modernity to make sense of 21st-century developments in political, social and economic life and thought. This review essay looks at two texts that, in different ways, test Koselleck's ideas in challenging and innovative ways. Lara's use of conceptual history to shed light on the debates over secularization demonstrates how concepts become central to struggles over the definition of politics – definitions which thereafter disclose the possibilities and set the agenda for future political action. Roitman continues Koselleck's interest in the concept of crisis and shows how conceptual history can be used to sharpen our awareness of undisclosed content and theoretical blind spots. Both show how conceptual history serves as a 'semantic check' on political concepts, demanding greater reflexivity and the setting of realistic political goals.